1997
DOI: 10.1111/j.1600-0420.1997.tb00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Corneoscleral discs excised from enucleated and non‐enucleated eyes are equally suitable for transplantation

Abstract: ABSTRACT.Purpose: To assess whether the biological quality of corneoscleral tissue dissected in situ is, after organ culture, comparable to that harvested after enucleation.Merhoh: Corneoscleral discs were prepared from 23 donor eyes, either after enucleation, under laminar flow conditions (right eyes; group 1) or by direct excision in situ (left eyes; group 2). Endothelial cell counts were made and the degree oftissue contamination assessed both prior to and upon termination of organ culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
(6 reference statements)
1
6
0
Order By: Relevance
“…Wiffen et al [10] report that 39 (31.2%) out of 125 corneas excised in situ had positive donor rim cultures versus only 152 (17.9%) out of 851 that were enucleated. Similar to these findings, various other microbiological studies also report that the risk of contamination was higher for donor corneas excised in situ versus those that were enucleated [10,14,21]. Even though we performed in situ excisions using a sterile portable electric trephine to harvest the corneal buttons at the Nagasaki Eye Bank, we did not find as many positive cultures as previous results.…”
Section: Discussionsupporting
confidence: 87%
“…Wiffen et al [10] report that 39 (31.2%) out of 125 corneas excised in situ had positive donor rim cultures versus only 152 (17.9%) out of 851 that were enucleated. Similar to these findings, various other microbiological studies also report that the risk of contamination was higher for donor corneas excised in situ versus those that were enucleated [10,14,21]. Even though we performed in situ excisions using a sterile portable electric trephine to harvest the corneal buttons at the Nagasaki Eye Bank, we did not find as many positive cultures as previous results.…”
Section: Discussionsupporting
confidence: 87%
“…2 Garweg et al showed that the adoption of the in situ excision technique might lead to permission for tissue collection being granted in a greater number of cases by the next of kin. 11 Our own experience (unpublished data) indicated that hospital staff were more likely to promote eye donation by in situ excision rather than whole globe enucleation.…”
Section: Discussionmentioning
confidence: 95%
“…The mean age of donors was 33.2 6 19.9 and 48.6 6 20.2 years in whole globe and in situ groups, respectively (P = 0.01). The median death retrieval time in whole globe group was 9 hours (range 1-19) and 4 hours (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] in in situ group (Wilcoxan rank sum test; P = 0.01). Thus, there was in fact a significant difference in mean age and median death retrieval time between the 2 groups.…”
Section: Preoperative Characteristicsmentioning
confidence: 99%
“…Previous investigators have been unable to show differences in most slit-lamp tissue characteristics or endothelial cell counts between these 2 techniques. 7,8 However, there is some suggestion that in situ extraction may be associated with a greater amount of tissue trauma. 7,9 The aforementioned studies concerning procurement technique involved analysis of relatively few corneal samples and did not assess the in situ procedure to determine its effect on tissue quality.…”
mentioning
confidence: 98%